Effect of styrene-butadiene-styrene (SBS) on laboratory properties of low-density polyethylene (LDPE)/ethylene-vinyl acetate (EVA) compound modified asphalt. (1st March 2022) - Hong, Zhe; Yan, Kezhen; Ge, Dongdong; Wang, Min; Li, Guokai; Li, Huili
Abstract: Waste plastic composed of polyethylene is one of the main factors of environmental pollution due to the slow degradation in nature, reuse waste materials to improve asphalt properties and relieve environmental pollution has more social and economic benefits. The main objective of this research was to assess the influence of styrene-butadiene-styrene (SBS) on the properties of low-density polyethylene (LDPE)/ethylene-vinyl acetate (EVA) modified asphalt, which aims to explore a feasible way to broaden the application of plastic in pavement engineering. Dynamic shear rheometer (DSR) and bending beam rheometer (BBR) tests were employed to evaluate the rheological behaviors of asphalt, and the temperature sensitivity explored by rotation viscosity. Furthermore, fluorescence microscopy (FM) and Flourier transform infrared (FTIR) spectroscopy tests were employed for microcosmic analysis. Test results indicated that SBS could increase rutting factor and reduce temperature sensitivity of LDPE/EVA compound modified asphalt. What's more, BBR test results suggested that SBS has positive effect on the low-temperature cracking resistance. Additionally, based on FM and FTIR tests, the cross-linking between polymer with asphalt further strengthened which may be due to some chemical reactions occurring. In the above consideration, SBS has positive effect on the properties of asphalt, especially the thermal cracking resistance. It is a feasible way to broaden the application of plastic in pavement engineering and beneficial for environmental protection that modification asphalt by SBS, LDPE and EVA.